Hubungan antara Paritas Dengan Posisi Menyusui Yang Benar Pada Ibu Nifas di RS Muhammadiyah Dan RS Muslimat Kabupaten Ponorogo - muniati murniati; Prasidharasmi Striratna Winayaiswari (Jurnal Delima Harapan, 2018)
Results of preliminary studies that have been conducted in the postpartum Hospital Muhammadiyah Ponorogo and Ponorogo in 10 respondents with observations on August 10, 2016 obtained 7 respondents (70%) with a breastfeeding is True Position, 3 respondents (30%) with a nursing position skilled. From 7 to mothers with less skilled nursing position in an entirely get primiparas. Thus allowing the lack of skilled due to a lack of experience on postpartum mother for the first time to breastfeed her baby. The purpose of this study to determine the relationship Parity with Breastfeeding Positions Right On Mother Postpartum hospital and the hospital's Muhammadiyah Ponorogo Ponorogo. The design study is an analytic correlational with cross sectional approach. The research location in Hospital’s Women Muhammadiyah Ponorogo Ponorogo, conducted in September 2016. The population is all breastfeeding mothers in Hospital’s Muhammadiyah Ponorogo Ponorogo, the month August 2016 the number of 30, with a sample of 30 people, with a purposive sampling techniques sampling. The independent variables are parity on postpartum mother and the dependent variable is the correct feeding position. The instrument of this research with interviews and observation sheet. Analysis of the data by using chi square test at the significant level of 0.05. Based on the results of parity On 22 Capital Ruling majority of respondents (73,3%) primiparas. Breastfeeding Correct Position On Mother Postpartum mostly 8 respondents (26,7%) with a disadvantage. No Parity Relationships with the Right Nursing Position On Postpartum Mothers in Hospital Muslimat Ponorogo and Muhammadiyah Ponorogo Ponorogo's Women, at significance level of 0.05 is thus obtained p = 0.000 p <α 0.05, Ha accepted that there Parity Relationships with Nursing Positions properly on Postpartum Mothers in Hospita’sMuslimat Ponorogo and Muhammadiyah Ponorogo Ponorogo, with a strong degree of closeness of relationship (0.683). Based on the results of the study are expected postpartum mothers to increase their knowledge and understanding of the importance of knowing the correct feeding position, especially for mothers primiparous.